Experimental Approach for the Evaluation of the Performance of a Satellite Module in the CanSat Form Factor for In Situ Monitoring and Remote Sensing Applications - Juan Sebastián Rodríguez; Andrés Yarce Botero; Diego Valle; Julián Gálvez- Serna; Francisco Botero (International Journal of Aerospace Engineering)
This article includes the phases of conceptualization and validation of a picosatellite prototype named Simple-2 for remote sensing activities using COTS (Commercial-Off-The-Shelf) components and the modular design methodology. To evaluate its performance and ensure the precision and accuracy of the measurements made by the satellite prototype, a methodology was designed and implemented for the characterization and qualification of CanSats (soda can satellites) through statistical tests and techniques of DoE (Design of Experiments) based on CubeSat aerospace standards and regulations, in the absence of official test procedures for these kinds of satellite form factor. For the above, two experimental units were used, and all the performance variables of the different satellite subsystems were discriminated. For the above, two experimental units were used, and all the performance variables of the different satellite subsystems were discriminated against. These were grouped according to the dependence of the treatments formulated in thermal and dynamic variables. For the tests of the first variables, a one-factor design was established using dependent samples on each of the treatments. Then, hypothesis tests were performed for equality of medians, using nonparametric analysis of the Kruskal-Wallis variance. Additionally, multivariate analysis of variance was carried out for nonparametric samples (nonparametric multivariate tests), and the application of post hoc multiple-range tests to identify the treatments that presented significant differences within a margin of acceptability. To know the dynamic response and ensure the structural integrity of the satellite module, shock, oscillation, and sinusoidal tests were applied through a shaker. Having applied the experimental methodology to the different units, the results of a real experiment are illustrated in which a high-altitude balloon was used through the application of nonparametric regression methods. This experiment’s interest measured thermodynamic variables and the concentration of pollutants in the stratosphere to corroborate the operating ranges planned in the above experiments using on-flight conditions and estimate the TLR (technology readiness level) of future prototypes.